CRISPR/Cas9 Epigenome Editing Potential for Rare Imprinting Diseases: A Review - Syding, Linn Amanda; Nickl, Petr; Kasparek, Petr; Sedlacek, Radislav (Cells, 2020)
Imprinting diseases (IDs) are rare congenital disorders caused by aberrant dosages of imprinted genes. Rare IDs are comprised by a group of several distinct disorders that share a great deal of homology in terms of genetic etiologies and symptoms. Disruption of genetic or epigenetic mechanisms can cause issues with regulating the expression of imprinted genes, thus leading to disease. Genetic mutations affect the imprinted genes, duplications, deletions, and uniparental disomy (UPD) are reoccurring phenomena causing imprinting diseases. Epigenetic alterations on methylation marks in imprinting control centers (ICRs) also alters the expression patterns and the majority of patients with rare IDs carries intact but either silenced or overexpressed imprinted genes. Canonical CRISPR/Cas9 editing relying on double-stranded DNA break repair has little to offer in terms of therapeutics for rare IDs. Instead CRISPR/Cas9 can be used in a more sophisticated way by targeting the epigenome. Catalytically dead Cas9 (dCas9) tethered with effector enzymes such as DNA de- and methyltransferases and histone code editors in addition to systems such as CRISPRa and CRISPRi have been shown to have high epigenome editing efficiency in eukaryotic cells. This new era of CRISPR epigenome editors could arguably be a game-changer for curing and treating rare IDs by refined activation and silencing of disturbed imprinted gene expression. This review describes major CRISPR-based epigenome editors and points out their potential use in research and therapy of rare imprinting diseases.
Keywords: diabetes mellitus; DNA Methylation; Angelmanův syndrom; genomový imprinting; Diabetes Mellitus; Angelman Syndrome; genomic imprinting; Epigenome; Infant, Newborn, Diseases; metylace DNA; Silver-Russell Syndrome; editace genu; vzácné nemoci; transcriptome editing; epigeneze genetická; Prader-Willi Syndrome; Silver-Russell syndrome; Silverův-Russellův syndrom; transient neonatal diabetes mellitus; Angelman syndrome; rare disease; Praderův-Williho syndrom; epigenome editing; Gene Editing; CRISPR-Cas Systems; lidé; Humans; Prader-Willi syndrome; epigenom; nemoci novorozenců; Genomic Imprinting; CRISPR-Cas systémy; Rare Diseases; Epigenesis, Genetic; CRISPR/Cas9